MicroRNAs Dysregulation and Metabolism in Multiple System Atrophy - Xiang, Chunchen; Han, Shunchang; Nao, Jianfei; Cong, Shuyan (Frontiers in Neuroscience, 2019)
Multiple system atrophy (MSA) is an adult onset, fatal disease, characterized by an accumulation of alpha-synuclein (α-syn) in oligodendroglial cells. MicroRNAs (miRNAs) are small non-coding RNAs involved in post-translational regulation and several biological processes. Disruption of miRNA-related pathways in the central nervous system (CNS) plays important roles in the pathogenesis of neurodegenerative diseases, including MSA. Whilst the exact mechanisms underlying miRNAs in the pathogenesis of MSA remains unclear, it is known that miRNAs can repress the translation of messenger RNAs (mRNAs) that regulate the following pathogenesis associated with MSA: autophagy; neuroinflammation; α-syn accumulation; synaptic transmission; oxidative stress, and apoptosis. In this review, the metabolism of miRNAs and their functional roles in the pathogenesis of MSA are discussed, thereby highlighting miRNAs as new potential biomarkers for the diagnosis of MSA and increasing understanding of the disease process.